Assesment of hematotoxic, oxidative and genotoxic damage potentials of fipronil in rainbow trout Oncorhynchus mykiss, Walbaum. (2nd January 2021) - Uçar, Arzu; Parlak, Veysel; Çilingir Yeltekin, Aslı; Özgeriş, Fatma Betül; Çağlar, Özge; Türkez, Hasan; Alak, Gonca; Atamanalp, Muhammed
Abstract: In this study, changes in the blood tissue of rainbow trout ( Oncorhynchus mykiss, Walbaum, 1792 ) caused by Fipronil (FP) insecticide were investigated using different biomarkers (Hematology parameters, superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), malondialdehyde (MDA), paraoxonase (PON), arylesterase (ARE), myeleperoxidase (MPO), micronucleus (MN), 8-hydroxy-2-deoxyguanosine (8-OHdG)) level and caspase-3 activity. Statistically significant alterations in hematology parameters occurred with FP effect. In blood tissue, dose-dependent inhibition was determined in SOD-CAT-GPX-PON and ARE enzyme activities, but MDA and MPO were induced statistically significant. The results of MN assay were compared with the control group and it was obtained that genotoxicity of different dose groups was similar. The level of 8-OHdG and the activity and caspase-3 examined in blood tissue was increased depending on the dose. It was determined with different biomarkers that this insecticide caused physiological stress changes in the tissues examined.